Dehumanization in Orwell's Dystopian Novels: An Overview on Totalitarianism and Ideology - Salim Kadhim Abbas , Asst. Prof. Dr. (lark, 2025)
Dehumanization of the individual and deformation of humankind are regarded as the prolific ideology of dystopia and dystopian States. Driven by this idea, the current paper renders an overview of how totalitarian regimes abuse their absolute power in order to exploit, deform, and overpower people that eventually resulted in the disaster of corruption in communities. Such an assumption could be applied to Orwell’s two novels, "Animal Farm" (1945) and "Nineteen Eighty-Four" (1949), as narrative texts.  It is hypothesized that the deformation of human nature is not intrinsic. Instead, it is the ideologies which are inhuman, and imposed by totalitarian regimes, that cause people's anguish physically and psychologically. To unfold such intricacy, this paper investigates the relationship between totalitarian power and ideology. The primary object of this study is to relate the concept of absolute power and power abuse exercised by totalitarianism, through its corrupt ideology, to corruption that leads to dystopia, then to the dehumanization, deformation of man, and reshaping human culture in a dystopian State. As analytical approaches, Marxist literary criticism and CDA are adopted to analyse the conceptual framework of this study.  The findings of this paper assert that the exercises of totalitarian regimes lead to corruption and create dystopia. Thus, it concludes that this could build up the misery of humankind, eventually leading to the mental and cultural deformation in dystopian States. The significance of this paper lies in tackling a dominant phenomenon in the history of humankind linked to totalitarianism. Thus, it contributes to providing a better understanding of the dehumanization of man and the inhuman situation under the unjust ruling of totalitarian regimes depicted in literary works.
Keywords: Totalitarianism, Culture, Ideology, "Dystopia", George Orwell, "Animal Farm", "Nineteen Eighty-Four"